Towards sustainable urea electro-oxidation: a thermodynamic and green chemistry evaluation of alternative pathways - Vyacheslav Protsenko (Royal Society Open Science, 2025)
This study presents a comparative thermodynamic analysis of various pathways for electrochemical hydrogen production coupled with the anodic oxidation of urea, offering a sustainable alternative to the conventional oxygen evolution reaction. For the first time, the feasibility and efficiency of these processes were evaluated using integrated green chemistry metrics, including atom economy and a newly proposed metric, electricity economy, which quantifies the theoretical minimum electrical energy required for the equilibrium formation of reaction products. The analysis demonstrated that urea-oxidation pathways generally require significantly less energy input than water electrolysis. Among the examined reactions, the oxidation of urea to gaseous nitrogen and carbonate ions was identified as the most efficient, with an electricity economy of –4650.83 J mol–1 and an atom economy of 6.4%. However, practical application is hindered by issues such as low product selectivity and high anodic potentials dictated by the redox thermodynamics of commonly used nickel-based catalysts. These findings underscore the need for next-generation electrocatalysts with enhanced selectivity and lower overpotentials to fully exploit the energetic advantages of urea oxidation for green hydrogen production.